Cast iron - May, Peter, 1951- (May, Peter, 1951- Enzo files, 2017)
In 1989, a killer dumped the body of twenty-year-old Lucie Martin into a picturesque lake in the West of France. Fourteen years later, during a summer heatwave, a drought exposed her remains. Yet when Enzo finds a flaw in the original evidence surrounding Lucie's murder, he opens a Pandora's box that not only raises old ghosts but endangers his entire family.--